The Effects of Economic Factors on Kuala Lumpur Stock Exchange Composite Index - Loo, Hooi Beng (1998)
An economic climate is a major factor in determining the primary trend of a stock market. The stock market, on the other hand, is often regarded as a reliable barometer of a country’s economy. In this study, Multivariate Time-Series Regression model are used to examine empirically the impact of foreign exchange rates, interest rate and inflation rate on Kuala Lumpur Stock Exchange Composite Index (CI). Pearson Correlation Matrices and Scatter Plots indicate that multicollinearity and heteroscedasticity exist among the selected currencies and independent variable. The finding in three-factor test using Multivariate Time-Series Regression with Auto regressive Moving Average technique indicates that coefficient of exchange rates and interest rate are significant, however, the coefficient of inflation rate is not significant. This study also indicates that both exchange rates and interest rate are negatively related to CI. This indicates that foreign exchange rates and interest rate do significantly and negatively affected the CI.